Developing a cultural competence inventory for nurses in China - D. Cai (2018)
© 2017 International Council of Nurses Aim: To develop and psychometrically test the Cultural Competence Inventory for Nurses in China. Background: Cultural competence is expected worldwide from nurses due to the increasing cultural diversity of people in healthcare establishments. Yet, no cultural competence framework or instrument for nurses has been identified to guide nursing practice in China where the cultural diversity of the populations and the characteristics of the healthcare system are different from those of the West. Methods: A review of literature and individual interviews among nurse experts generated 74 items, which were evaluated by six experts in transcultural nursing. A stratified random sampling technique was used to recruit 520 Chinese nurses for the field test. Construct validity and internal consistency reliability of the instrument were estimated by exploratory factor analysis and Cronbach's alpha, respectively. The data were collected from May 2015 to January 2016. Results: The final instrument consists of 29 items in five dimensions, namely ‘cultural awareness, cultural respect, cultural knowledge, cultural understanding and cultural skills’. Cronbach's alpha for the instrument was 0.94, with a range of 0.79–0.92 for the individual dimensions. The evidence for contrast-group validity (P < 0.001) was also obtained. Conclusion: The study provides evidence that the Cultural Competence Inventory for Nurses in China is reliable, valid and culturally sensitive for measuring nurses’ cultural competence. The instrument development process facilitates the understanding of cultural competence globally. Implications for nursing and nursing policy: Cultural competence of nurses can be evaluated for self-development, workforce management and quality assurance. The instrument can also serve as the foundation to develop education curricula and nursing procedures or protocols to improve culturally competent nursing practice.